Meningkatkan Keterampilan Kolaborasi Siswa SMP Negeri Terawas melalui Penggunaan Model Pembelajaran Inkuiri Terbimbing - Preti Alhayyu Utami; Ovilia Putri Utami Gumay; Ahmad Amin (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
This study aims to analyze the effect of implementing the Guided Inquiry learning model on improving collaboration skills and science learning outcomes among students at SMP Negeri Terawas. The study was motivated by students' low collaboration skills—evidenced by suboptimal abilities in cooperation, communication, responsibility, flexibility, and reaching consensus during group work—as well as low science learning outcomes. A quantitative approach was employed using a pre-experimental design, specifically the One-Group Pretest-Posttest Design. The research subjects consisted of 30 seventh-grade students selected via a saturated sampling technique. Data were collected using collaboration skill observation sheets and learning outcome tests, then analyzed using descriptive statistics and the N-Gain test. The results indicate that the average collaboration skill score increased from 45.86 to 72.96, with an N-Gain value of 0.588, falling into the medium category. Additionally, the average learning outcome score rose from 20.33 in the pretest to 78.50 in the posttest. These findings demonstrate that the Guided Inquiry learning model is effective in enhancing collaboration skills and science learning outcomes through inquiry, discussion, and problem-solving activities that foster active student engagement within a student-centered learning environment.